Oral and maxillofacial symptoms of patients with IgG4-related disease: The meaning of a labial minor salivary gland biopsy. Issue 5 (September 2018) - Tsuchida, Shuji; Wakui, Takahiro; Okubo, Maki; Uchida, Daisuke; Kawamata, Hitoshi
Abstract: Objective: We examined the symptoms in the oral and maxillofacial regions of patients with IgG4-related disease (IgG4-RD) and considered the meaning of a labial minor salivary gland (LMSG) biopsy in such patients. Methods: Sixty-three patients diagnosed with IgG4-RD in our hospital, were examined for symptoms in the oral and maxillofacial regions. Out of the 24 patients who were referred to our department, 20 underwent immunohistochemical analysis of the LMSG for IgG and IgG4. Results: Symptoms in the oral and maxillofacial region were observed in 18 of the 63 patients. Out of the 18 patients, 15 had swelling of the submandibular glands, 5 had severe xerostomia, 4 had swelling of the parotid glands, and 2 experienced irritation and pain while eating. IgG4-positive plasma cells in the LMSG biopsy samples were observed in 19 of the 20 patients examined (95%). In 6 patients, more than 40% of the infiltrated plasma cells were positive for IgG4; in 2 patients, more than 30% of the plasma cells were positive; in 3 patients, more than 20% of the plasma cells were positive; in 7 patients, more than 10% of the plasma cells were positive; in 1 patient, more than 5% of the plasma cells were positive. Conclusions: Out of the 63 patients, only 18 (29%) had symptoms in the oral and maxillofacial regions. Infiltration of IgG4-positive plasma cells, regardless of their intensity in the non-symptomatic LMSG, might be considered as one of the important symptoms of IgG4-RD.